Catastrophe Containment and Relief Trust-Fifth Tranche of Debt Service Relief in The Context of The COVID-19 Pandemic. (Policy Papers; Policy Paper ;, 2021)
The Executive Board approved a two-step approach consisting of (i) an immediate approval of the disbursement of a fourth tranche of debt service relief to all qualified beneficiary countries covering the period from October 16, 2021 through January 10, 2022, and (ii) consideration by January 2022 of a final tranche of CCRT debt service relief through April 13, 2022 based on a brief Board paper with an assessment of resources at that time. In accordance with the two-step approach, this paper provides a brief overview on recent developments in CCRT-eligible countries followed by an update on the CCRT's funding status and resources assessment.